Nano patterning of cone dots and nano constrictions of negative e-beam resist for single electron transistor fabrication - Sutikno, Madnasri; Uda, Hashim; Zul Azhar, Zahid Jamal (Springer New York, 2009)
Link to publisher's homepage at http://www.springerlink.com